"A herder's duty is to think": landscape partitioning and folk habitats of Mongolian herders in a mountain forest steppe (Khuvsugul-Murun region) - B. Gantuya; Á. Avar; D. Babai; Á. Molnár; Zs Molnár (BMC, 2019)
Abstract Background Traditional habitat knowledge, like the classification of folk habitats and how people partition their landscape into habitats, is an emerging but still understudied part of traditional ecological knowledge. Our objectives were to reconstruct the folk habitats and the partitioning of the landscape into these folk habitats by Mongolian herders in Northern Mongolia and to compare it with other Northern Hemisphere boreal-temperate classifications. Methods The study area is located in Seruun Gilad (Khuvsugul province) and belongs to the mountain forest steppe of the Khangai region (dominated by meadow steppes and larch forests). Most herder families use the area for summer pasturing. Data collection was based on indoor and outdoor, structured and semi-structured interviews and interviews during landscape walks and participatory fieldwork. We interviewed 20 people using 76+ photos of plant species and 25+ photos of habitats and asked them to name and describe the habitats and describe the habitat preferences of the species. Results Mongolian herders distinguished at least 88 folk habitat categories and knew well the habitat preferences of the 76 plant species. They argued that a herder has to be observant of nature. The habitat classification was moderately lexicalized, with many descriptive expressions. Most habitats (77%) belonged to the meso-scale, while macro-scale habitats (like taiga, Gobi) and micro-scale habitats (like marmot burrow, top of the tussock) were few. Habitat names did not reflect directly the usefulness of the habitat. Classification was multidimensional; key dimensions were geomorphological and edaphic. There were some species (e.g., botyuul, hyag, shireg) and species groups (hot plants, leafy plants) that were often used to describe habitat types. Conclusions Landscape partitionings in the Northern Hemisphere differed considerably in the importance of various dimensions used, with edaphic, geomorphological, hydrological, and dominant species-based dimensions having higher importance, while land use, successional, and zoological dimensions having lower importance. We argue that conducting research on folk habitats will contribute to a deeper understanding of how nature is perceived by locals and to a more efficient management of the Mongolian pastures.